2020
DOI: 10.3389/fphar.2020.00742
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lycium barbarum Polysaccharide on Endoplasmic Reticulum Stress and Oxidative Stress in Obese Mice

Abstract: Background: The incidence of obesity-associated decline in male fertility has increased over the years. Lycium barbarum polysaccharide (LBP), a natural plant polysaccharide extracted from the Chinese herb L. barbarum has shown promising therapeutic effects in overcoming the same.Aim: This study aimed to investigate the protective effect of LBP on the testes of obese mice.Methods: Following administration of LBP to high-fat diet-induced obese mice for 35 days, serum, sperm, and testis samples were obtained for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 41 publications
0
17
0
1
Order By: Relevance
“…In addition, numerous studies have shown that oxidative stress increases the production of free radicals in fat and muscle cells, decreases antioxidant substances, and increases the accumulation of oxidation products, such as MDA [ 33 ]. It has been proven that the increase in antioxidants such as SOD and GSH-Px can eliminate reactive oxygen species and further improve oxidative stress [ 34 ]. Simulating mice using STZ results in autophosphorylation of insulin receptors and increased activity of intrinsic tyrosine kinase, phosphotyrosine phosphatase, which in turn leads to inhibition of insulin signaling, disruption of glucose and energy metabolism in the brain, and induction of impaired consciousness.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, numerous studies have shown that oxidative stress increases the production of free radicals in fat and muscle cells, decreases antioxidant substances, and increases the accumulation of oxidation products, such as MDA [ 33 ]. It has been proven that the increase in antioxidants such as SOD and GSH-Px can eliminate reactive oxygen species and further improve oxidative stress [ 34 ]. Simulating mice using STZ results in autophosphorylation of insulin receptors and increased activity of intrinsic tyrosine kinase, phosphotyrosine phosphatase, which in turn leads to inhibition of insulin signaling, disruption of glucose and energy metabolism in the brain, and induction of impaired consciousness.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, LBPs dietary supplementation increased T-AOC and GSH-Px levels but decreased MDA production. Yang F. et al (2020) reported that LBPs dietary supplementation relieved oxidative stress in high fat diet-induced obese mice. Liu et al (2021b) found that LBPs supplementation reduced myocardial oxidative stress via activation of the nuclear factor erythroid-2 antioxidant signal pathway.…”
Section: Discussionmentioning
confidence: 99%
“…LBPs have been shown in many studies to reduce oxidative damage by regulating endoplasmic reticulum stress (ERS). Yang et al [ 115 ] found that LBPs intervention can improve ERS and oxidative stress, as well as increase the expression of antioxidase-related indexes in the testis of obese mice induced by the high-fat diet. Moreover, LBPs can ERS signaling by inhibiting the activation of p-eIF2α and GRP78-CHOP, reducing oxidative stress [ 115 ] (see Figure 5 ).…”
Section: Molecular Mechanisms Related To the Antioxidant Effect Of Lbpsmentioning
confidence: 99%